What factors shape AI media Islamic education? - Setiyawan, Adhi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2025)
Purpose – The development of Artificial Intelligence (AI) has driven significant transformations in the development of learning media, including in the field of Pendidikan Agama Islam (PAI). Despite its potential, AI implementation in PAI raises pedagogical, ethical, and socio-cultural challenges. This study aims to synthesize conceptual developments of AI in PAI learning media through scientific mapping, addressing the lack of comprehensive studies that systematically identify key development factors grounded in pedagogy, Islamic values, and the context of Islamic higher education. This synthesis is essential to mitigate the misuse of generative AI and to support the development of ethical and relevant learning media. Design/methods/approach – This study employed a bibliometric meta-analysis using Bibliometrix in R Studio (biblioshiny), analyzing 446 selected publications from reputable sources related to AI, learning media, and Islamic education. Findings – The analysis identified technically intensive themes, including machine learning, deep learning, data mining, information retrieval, natural language processing, and text processing. Broader strategic themes such as digital transformation, big data, and investment reflect system-level implementation trends. Conceptual mapping revealed key factor clusters encompassing pedagogical, technological, ethical, social, and institutional dimensions. These findings provide a conceptual foundation for developing integrative, contextual, and sustainable AI-based PAI learning media. Research implications/limitations – The study is limited by time and funding constraints, which restricted data sources and prevented deeper comparative analyses across regions and educational levels. Originality/value – This study offers originality by providing a systematic conceptual synthesis of AI-based learning media development. By integrating pedagogical principles, Islamic values, and socio-cultural considerations into a bibliometric conceptual mapping, this study provides a new integrative framework that supports the ethical, contextual, and sustainable use of AI in Islamic Religious Education learning media development.